Method for producing sulfide solid electrolyte

By mixing raw materials of lithium, phosphorus, sulfur and halogen atoms in the solvent and excessive use of elemental sulfur to generate free radicals of sulfur, the problems of long reaction time and low electrolyte purity in the prior art are solved, and high ionic conductivity is achieved and efficiently produced sulfide solid electrolytes.

CN119487586APending Publication Date: 2025-02-18IDEMITSU KOSAN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380050875.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-10
Filing Date
2023-07-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when manufacturing sulfide solid electrolytes with high ionic conductivity, the reaction time is long, the production efficiency is low, and it is easy to lead to a decrease in the purity of the electrolyte and the ionic conductivity.

Method used

By mixing raw materials containing lithium, phosphorus, sulfur and halogen atoms in the solvent and excessive use of elemental sulfur to generate free radicals of sulfur, promoting reaction with other raw materials, forming a sulfide solid electrolyte with high ionic conductivity.

Benefits of technology

It realizes efficiently providing sulfide solid electrolyte with improved ionic conductivity, simplifying the production process and improving the purity and ionic conductivity of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487586A_ABST
    Figure CN119487586A_ABST
Patent Text Reader

Abstract

A method for producing a sulfide solid electrolyte, comprising: mixing, in a solvent, raw material-containing substances including a plurality of raw materials including at least one type of atom selected from among a lithium atom, a phosphorus atom, a sulfur atom, and a halogen atom; and then heating, the raw material-containing material including elemental sulfur and lithium sulfide, the elemental sulfur being used more than 1.0 mol with respect to 1.0 mol of the lithium sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a sulfide solid electrolyte. Background Art

[0002] In recent years, with the rapid popularization of information-related devices or communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has also received attention. In the past, in batteries used for such purposes, electrolytes containing flammable organic solvents were used, but by making the battery fully solid, the safety device is simplified because no flammable organic solvent is used in the battery, and the manufacturing cost and productivity are excellent. Therefore, the development of batteries in which the electrolyte is replaced by a solid electrolyte layer is carried out.

[0003] As a method for manufacturing a solid electrolyte for a solid electrolyte layer, it is roughly divided into a solid phase method and a liquid phase method, and the liquid phase method includes a uniform method in which a solid electrolyte material is completely dissolved in a solvent, and an inhomogeneous method in which a solid electrolyte material is not completely dissolved but a suspension coexists with solid and liquid. For example, as a uniform method in the liquid phase method, a method of dissolving a solid electrolyte in a solvent to reprecipitate it is known (for example, refer to patent document 1), and as an inhomogeneous method, a method of reacting solid electrolyte raw materials such as lithium sulfide in a solvent containing a polar aprotic solvent is known (for example, refer to patent documents 2 and 3), and a method for manufacturing a solid electrolyte using a specific compound having an amino group as a complexing agent (for example, refer to patent documents 4 and 5). Non-patent document 1 records: using tetrahydrofuran and ethanol, a tetrahydrofuran-ethanol precursor solution of Li6PS5Br is prepared, which is dried and heated to produce a solid electrolyte having a argyrodite-type crystal structure and the argyrodite-type crystal structure having a composition of Li6PS5Br.

[0004] In addition, non-patent documents 2 and 3 describe that Li2S, P2S5 and S (7:3:x (x=3, 5 and 7) molar ratio) are added to a mixed solvent (1:1:0.05 (volume ratio)) of acetonitrile, tetrahydrofuran and ethanol to generate lithium polysulfide and highly reactive sulfur radicals, and after stirring for several minutes, the mixture is dried under vacuum and heated at a heating temperature of 270°C, 350°C, etc. to produce Li7P3S 11 A crystalline solid electrolyte with a composition of

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-191899

[0008] Patent Document 2: International Publication No. 2014 / 192309

[0009] Patent Document 3: International Publication No. 2018 / 054709

[0010] Patent Document 4: International Publication No. 2020 / 105737

[0011] Patent Document 5: International Publication No. 2021 / 230189

[0012] Non-patent literature

[0013] Non-patent document 1: J. Mater. Chem. A, 2019, 7, 558-566

[0014] Non-patent document 2: 62nd Battery Symposium Draft Paper, published on November 29, 2021, All-solid-state batteries / sulfide electrolytes, 3E01

[0015] Non-patent literature 3: Adv. Energy Sustainability Res., 2022, 3, 2200019 Summary of the invention

[0016] Technical problem to be solved by the invention

[0017] The present invention has been made in view of the above circumstances, and an object of the present invention is to efficiently provide a sulfide solid electrolyte having improved ion conductivity.

[0018] Solutions for solving the above technical problems

[0019] The method for producing the sulfide solid electrolyte of the present invention is:

[0020] A method for manufacturing a sulfide solid electrolyte, comprising:

[0021] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0022] Then heating,

[0023] The raw material contains elemental sulfur and lithium sulfide,

[0024] The amount of the elemental sulfur used is greater than 1.0 mol relative to 1.0 mol of the lithium sulfide.

[0025] Effects of the Invention

[0026] According to the present invention, a sulfide solid electrolyte having improved ion conductivity can be provided efficiently. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0028] Figure 2 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0029] Figure 3 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0030] Figure 4 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0031] Figure 5 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0032] Figure 6 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0033] Figure 7 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0034] Figure 8 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0035] Fig. 9 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0036] Fig.10 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0037] Fig.11 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0038] Fig.12 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0039] Fig.13 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0040] Fig.14 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0041] Fig.15 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0042] Fig.16 These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0043] Fig.17These are X-ray diffraction spectra of powders obtained in Examples and Comparative Examples.

[0044] Fig.18 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0045] Fig.19 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0046] Fig. 20 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0047] Fig.21 This is an X-ray diffraction spectrum of the powder obtained in the example.

[0048] Fig. 22 This is an X-ray diffraction spectrum of the powder obtained in the example. DETAILED DESCRIPTION

[0049] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limit values ​​involved in the numerical ranges of "above", "below", and "to" are values ​​that can be arbitrarily combined, and the values ​​of the embodiments can also be used as the upper and lower limit values. In addition, preferred provisions can be adopted arbitrarily. That is, a preferred provision can be combined with another preferred provision or multiple provisions. It can be said that the combination of preferred provisions is more preferred.

[0050] (Discovery made by the present inventors to complete the present invention)

[0051] The present inventors have conducted intensive studies to solve the above-mentioned technical problems, and as a result, have found the following matters, thereby completing the present invention.

[0052] In recent years, with the goal of practical application of all-solid-state batteries, the liquid phase method has attracted attention as a method that can be synthesized simply and in large quantities in addition to versatility and applicability. As a solid phase method, a method represented by a mechanical grinding method can be cited, in which a solid electrolyte raw material is crushed and mixed with a pulverizer and reacted to obtain a solid electrolyte, but due to the high cost of equipment and the need for a large amount of initial investment, it is difficult to reduce costs.

[0053] On the other hand, regarding the liquid phase method, for example, in the method described in Patent Document 1, Li2S and P2S5 (80:20) are subjected to mechanical grinding for 20 hours, dissolved in N-methylformamide (NMF), and dried to obtain a solid electrolyte, which requires 20 hours of mechanical grinding. In the method described in Patent Document 2, Li2S and P2S5 are contacted for 24 hours in a mixed solvent of a hydrocarbon solvent (toluene) and a polar aprotic solvent (tetrahydrofuran) to react, and in the method described in Patent Document 3, when Li3PS4·DME (electrolyte precursor; complex) is produced in dimethoxyethane (DME), stirring is performed for about 10 days. In addition, in the method using a complexing agent described in Patent Documents 4 and 5, the reaction is carried out by stirring the solid electrolyte raw material and the complexing agent together for 12 to 72 hours, and further for more than 72 hours. In addition, in the method described in Non-Patent Document 1, the reaction is also carried out overnight, that is, the reaction is carried out for about 12 hours. As described above, since the reaction time is long in the conventional production method, better production efficiency is required.

[0054] In addition, in the method described in non-patent document 1, drying is performed for 3 hours to remove tetrahydrofuran and ethanol. However, oxides as impurities are sometimes generated due to the reaction of a portion of the residual ethanol with the solid electrolyte. A portion of Li2S, which is commonly used as a raw material for solid electrolytes, reacts with alcohol solvents such as ethanol to generate alcohol lithium such as lithium ethanol, which does not contribute to the reaction with raw materials such as phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)) commonly used with Li2S. Therefore, there is a situation where the purity of the sulfide solid electrolyte is reduced and the ion conductivity is reduced, and quality improvement is also required.

[0055] In the methods described in non-patent documents 2 and 3, a crystalline sulfide solid electrolyte is obtained by stirring for several minutes, drying for 1 hour, and heating for 1 hour, which can be said to have excellent production efficiency. However, since it does not contain halogen atoms, the ionic conductivity is about 0.9 to 1.3 mS / cm, which cannot be said to be a sulfide solid electrolyte with high ionic conductivity. Moreover, in these non-patent documents, it is recorded that ethanol acts on lithium of lithium polysulfide to generate highly reactive sulfur radicals. Therefore, it is also conceivable that if a lithium halide containing Li like Li2S is used as a raw material, the mechanism for the generation of sulfur radicals is hindered and an efficient reaction cannot be carried out.

[0056] Thus, the prior art has both advantages and disadvantages, and there is room for improvement in producing sulfide solid electrolytes with high ionic conductivity at higher production efficiency.

[0057] Therefore, the present inventors focused on elemental sulfur as a raw material and studied the use of a raw material containing halogen atoms in order to improve ion conductivity using elemental sulfur as a raw material. As a result, it was found that a sulfide solid electrolyte with improved ion conductivity can be obtained in a very short time by using an excess amount of elemental sulfur.

[0058] (Various Aspects of the Present Embodiment)

[0059] The method for producing a sulfide solid electrolyte according to the first aspect of the present embodiment is as follows:

[0060] A method for manufacturing a sulfide solid electrolyte, comprising:

[0061] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0062] Then heating,

[0063] The raw material contains elemental sulfur and lithium sulfide,

[0064] The amount of the elemental sulfur used is greater than 1.0 mol relative to 1.0 mol of the lithium sulfide.

[0065] In the method for producing a sulfide solid electrolyte of the present embodiment, it is necessary to use elemental sulfur and lithium sulfide in combination as raw materials. It is considered that elemental sulfur reacts with lithium sulfide in a solvent to become a polysulfide of lithium and generates sulfur free radicals. Sulfur free radicals are highly reactive and promote reactions with other raw materials such as phosphorus pentasulfide and other raw materials containing halogen atoms to generate soluble polysulfides (hereinafter also referred to as "polysulfides") which are precursors of sulfide solid electrolytes (hereinafter also referred to as "electrolyte precursors"). It is considered that by decomposing the polysulfide by heating or the like, a sulfide solid electrolyte with improved ionic conductivity can be efficiently produced.

[0066] In addition, the amount of elemental sulfur used is more than 1.0 mol relative to 1.0 mol of lithium sulfide, and is used in an excess amount. The amount used is an excess amount compared to the sulfur atoms required for the desired sulfide solid electrolyte, and the details will be described later. In this way, by using an excess amount of elemental sulfur, the generation of the above-mentioned sulfur free radicals is promoted, so that as a result, a sulfide solid electrolyte with improved ion conductivity can be efficiently manufactured.

[0067] By mixing the above-mentioned raw material contents, a precursor of a sulfide solid electrolyte, an amorphous sulfide solid electrolyte, and a crystalline sulfide solid electrolyte that are further heated can be mainly generated. By mixing, a soluble polysulfide is generated as an electrolyte precursor, and by heating, the polysulfide is decomposed to become an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte, and the crystallinity of the crystalline sulfide solid electrolyte is improved. In addition, the solvent is also removed. Therefore, in the manufacturing method of this embodiment, it can be said that heating is mainly performed for the decomposition of polysulfides, the removal of solvents and crystallization. In addition, the removal of elemental sulfur generated by the decomposition of polysulfides can also be performed by evaporation achieved by heating, but this can also be applied to methods other than heating such as solvent washing and hydrodesulfurization.

[0068] A method for producing a sulfide solid electrolyte according to a second aspect of the present embodiment is, in the above-mentioned first aspect,

[0069] The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.

[0070] If the sulfide solid electrolyte contains halogen atoms, it has high ion conductivity. Among them, by containing any of chlorine atoms, bromine atoms, and iodine atoms, it is easy to form an argyrodite-type crystal structure and a sulfide crystal lithium superion conductor region type II crystal structure that show particularly high ion conductivity.

[0071] A method for producing a sulfide solid electrolyte according to a third aspect of the present embodiment is, in the first or second aspect,

[0072] The solvent is an organic solvent containing at least one atom selected from oxygen atoms and nitrogen atoms,

[0073] A fourth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to third methods described above,

[0074] The solvent is at least one organic solvent selected from alcohol solvents, ether solvents and nitrile solvents.

[0075] If a solvent containing heteroatoms is used as a solvent, the generation of sulfur free radicals is promoted through the lithium polysulfide produced by the reaction of elemental sulfur and lithium sulfide. Since the reactivity of sulfur free radicals is high, they act on other raw materials such as phosphorus pentasulfide and other raw materials containing halogen atoms, react with lithium sulfide or lithium polysulfide, and thus promote the generation of soluble polysulfides. This soluble polysulfide is a precursor of a sulfide solid electrolyte. By heating, the polysulfide decomposes and quickly becomes an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte, and the crystallinity of the crystalline sulfide solid electrolyte is improved. As a result, a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.

[0076] In addition, as such a solvent containing heteroatoms, at least any one of an alcohol solvent, an ether solvent and a nitrile solvent is preferably used. By using these solvents, the effect of using the above-mentioned solvent containing heteroatoms, i.e. the generation of free radicals of sulfur and the formation of electrolyte precursors (polysulfides) are promoted. In addition, by using alcohol solvents, ether solvents and nitrile solvents, the generation of free radicals of sulfur and the formation of electrolyte precursors (polysulfides) are promoted in a balanced manner. As a result, a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.

[0077] A fifth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to fourth methods described above,

[0078] The solvent comprises an alcohol solvent,

[0079] A sixth method for producing a sulfide solid electrolyte is, in the first to fifth methods,

[0080] The solvent includes an alcohol solvent and at least one organic solvent selected from an ether solvent and a nitrile solvent.

[0081] Among the solvents containing heteroatoms, the alcohol solvents, ether solvents and nitrile solvents are effective in the generation of sulfur free radicals and the formation of electrolyte precursors (polysulfides), and alcohol solvents are particularly effective in promoting the generation of sulfur free radicals and the formation of electrolyte precursors (polysulfides). By using alcohol solvents, a sulfide solid electrolyte with less impurities and high ion conductivity can be produced more efficiently.

[0082] In addition, regarding the alcohol solvent, ether solvent and nitrile solvent, it is also effective to use an alcohol solvent and at least one of an ether solvent and a nitrile solvent. This can easily promote the generation of sulfur radicals and the formation of an electrolyte precursor (polysulfide) in a well-balanced manner.

[0083] A seventh method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to sixth methods described above,

[0084] The solvent is an organic solvent including an alcohol solvent, an ether solvent and a nitrile solvent.

[0085] An eighth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in any one of the fifth to seventh aspects,

[0086] The alcohol solvent is used in an amount of 0.005 mol or more and 20.0 mol or less relative to 1.0 mol of the lithium sulfide.

[0087] A ninth aspect of the method for producing a sulfide solid electrolyte is, in the sixth to eighth aspects,

[0088] The total amount of the ether solvent and the nitrile solvent used is 2.0 parts by volume or more and 10000.0 parts by volume or less relative to 1.0 part by volume of the alcohol solvent used.

[0089] As described above, by using a solvent containing a heteroatom, the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted, wherein, by using an alcohol solvent, the formation effect of the electrolyte precursor (polysulfide) is improved. In this case, by setting the usage of the alcohol solvent to the above range, the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) can be further promoted. In addition, by making the total usage of the ether solvent and the nitrile solvent to the above range, the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are further promoted.

[0090] A method for producing a sulfide solid electrolyte according to a tenth aspect of the present embodiment is, in the first to ninth aspects,

[0091] The heating temperature during the heating is 20°C to 500°C.

[0092] The eleventh embodiment of the method for producing a sulfide solid electrolyte is, in the first to tenth embodiments,

[0093] The heating is performed by first heating at a heating temperature of 20° C. or higher and lower than 150° C. and second heating at a heating temperature of 150° C. or higher and 500° C. or lower.

[0094] As described above, in the manufacturing method of this embodiment, heating is mainly performed for decomposition of the electrolyte precursor (polysulfide), removal of the solvent and crystallization. If the heating temperature during heating is within the above range, crystallization can be performed while removing the solvent more efficiently and reliably.

[0095] In addition, by performing heating in multiple stages such as the first heating and the second heating, decomposition of polysulfides, removal of solvents and crystallization can be performed more efficiently. Furthermore, by performing heating, elemental sulfur generated by decomposition of polysulfides can also be removed. Removal of elemental sulfur is not limited to heating, and can also be performed by other methods such as solvent washing and hydrodesulfurization.

[0096] A twelfth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in the above-mentioned first to eleventh aspects,

[0097] When performing the mixing, the raw materials are mixed simultaneously,

[0098] A thirteenth aspect is a method for producing a sulfide solid electrolyte, wherein in the first to eleventh aspects,

[0099] In the mixing, a raw material group 1 including a part of raw materials selected from the raw materials is mixed, and then a raw material group 2 including raw materials other than the part of raw materials is mixed.

[0100] In the manufacturing method of this embodiment, the supply order of the raw materials is not particularly limited. From the perspective of easier operation, it is preferred to mix all the raw materials at the same time (also referred to as "one-time mixing"). In addition, if higher solubility and ion conductivity of the raw materials are considered, it is preferred to divide the raw materials into two groups as described later and mix them in sequence (also referred to as "batch mixing").

[0101] In the production method of the present embodiment, whether to mix all at once or to mix in batches may be appropriately selected depending on whether ease of workability or ion conductivity is given priority.

[0102] A method for producing a sulfide solid electrolyte according to a fourteenth aspect of the present embodiment is, in the thirteenth aspect,

[0103] The raw material group 1 contains elemental sulfur,

[0104] The method for producing a sulfide solid electrolyte according to the fifteenth aspect is, in the thirteenth or fourteenth aspect,

[0105] The raw material group 1 includes a raw material containing at least one atom selected from lithium atoms, phosphorus atoms, and sulfur atoms, elemental sulfur, and lithium sulfide, and the raw material group 2 includes a raw material containing a halogen atom.

[0106] When the raw materials are mixed in two stages, it is preferred that raw material group 1 contains elemental sulfur, that is, elemental sulfur is mixed first. Since sulfur radicals can be formed first, a sulfide solid electrolyte with improved ion conductivity can be efficiently produced.

[0107] In addition, from the perspective of reducing the residual amount of raw materials and obtaining higher ion conductivity, it is preferred to allocate the raw materials containing at least one atom selected from lithium atoms, phosphorus atoms and sulfur atoms and the raw materials containing halogen atoms to either raw material groups 1 and 2.

[0108] From the viewpoint of efficiently producing a sulfide solid electrolyte with improved ion conductivity by further promoting the formation of sulfur radicals via lithium polysulfides and further promoting the formation of electrolyte precursors, it is particularly preferred that raw material group 1 includes: a raw material containing at least one atom selected from lithium atoms, phosphorus atoms and sulfur atoms, elemental sulfur and lithium sulfide, and that raw material group 2 includes: a raw material containing halogen atoms.

[0109] A sixteenth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to fifteenth methods described above,

[0110] A crystalline sulfide solid electrolyte having an argyrodite-type crystal structure or a sulfide crystalline lithium superion conductor region-type II crystal structure is produced.

[0111] In the manufacturing method of the present embodiment, a desired sulfide solid electrolyte can be manufactured by changing the type and blending ratio of the solid electrolyte raw material contained in the raw material content. Crystalline sulfide solid electrolytes having an argyrodite-type crystal structure and crystalline sulfide solid electrolytes having a sulfide crystalline lithium superion conductor region II-type crystal structure are known to be sulfide solid electrolytes having extremely high ion conductivity, and are preferred as the sulfide solid electrolytes intended to be obtained by the manufacturing method of the present embodiment.

[0112] (Sulfide solid electrolyte)

[0113] In this specification, "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere. The sulfide solid electrolyte in this embodiment is a solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and having ion conductivity due to lithium atoms.

[0114] The “sulfide solid electrolyte” includes both an amorphous sulfide solid electrolyte and a crystalline sulfide solid electrolyte.

[0115] In this specification, the crystalline sulfide solid electrolyte refers to a sulfide solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and is a material that is independent of the presence or absence of a peak derived from a raw material of the sulfide solid electrolyte. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from a solid electrolyte, and a part of it may be a crystal structure derived from the solid electrolyte, or all of it may be a crystal structure derived from the solid electrolyte. Furthermore, as long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, a part of it may also include an amorphous sulfide solid electrolyte. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating an amorphous sulfide solid electrolyte to a crystallization temperature or higher.

[0116] In this specification, an amorphous sulfide solid electrolyte means an X-ray diffraction pattern having a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the raw material of the sulfide solid electrolyte.

[0117] [Method for producing sulfide solid electrolyte]

[0118] The method for producing the sulfide solid electrolyte of the present embodiment is as follows:

[0119] A method for manufacturing a sulfide solid electrolyte, comprising:

[0120] mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; and

[0121] Then heating,

[0122] The raw material contains elemental sulfur and lithium sulfide,

[0123] The amount of the elemental sulfur used is greater than 1.0 mol relative to 1.0 mol of the lithium sulfide.

[0124] 〔Contents of mixed raw materials〕

[0125] The production method of this embodiment includes mixing a raw material-containing material including a plurality of raw materials including at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in a solvent.

[0126] First, the production method of this embodiment will be described starting from the raw material contents.

[0127] (Ingredients contained in raw materials)

[0128] The raw material content used in this embodiment is a content containing multiple raw materials containing at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, and contains elemental sulfur and lithium sulfide. That is, the raw material content is a content containing at least elemental sulfur and lithium sulfide, and further contains multiple raw materials containing at least one atom selected from lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.

[0129] Representative examples of the raw materials included in the raw material content include: lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), various phosphorus iodides (PI3, P2I4), and the like; thiophosphoryl fluoride (PS F3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), thiophosphoryl fluoride dibromide (PSBr2F) and other halogenated thiophosphoryls; raw materials composed of at least two atoms selected from the above four atoms, halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), iodine (I2), preferably chlorine (Cl2), bromine (Br2), iodine (I2).

[0130] Substances that can be used as raw materials other than the above-mentioned ones include, for example, raw materials containing at least one atom selected from the above-mentioned four atoms and atoms other than the four atoms. More specifically, they include: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like.

[0131] Among the above, preferred are: lithium sulfide; phosphorus sulfide such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2); lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide. In addition, when oxygen atoms are introduced into the solid electrolyte, lithium oxide, lithium hydroxide, and phosphoric acid compounds such as lithium phosphate are preferred.

[0132] As the halogen atom, a chlorine atom, a bromine atom and an iodine atom are preferred, and at least one selected from these is preferred.

[0133] Therefore, as the above-mentioned lithium halide, lithium chloride, lithium bromide, and lithium iodide are preferred, and as the halogen element, chlorine (Cl2), bromine (Br2), and iodine (I2) are preferred. In addition, they can be used alone or in combination of multiple types.

[0134] As the combination of raw materials, for example, preferably there can be mentioned a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide, and a combination of lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element. As the lithium halide, preferably there is lithium chloride, lithium bromide and lithium iodide. As the halogen element, preferably there is chlorine, bromine and iodine.

[0135] In this embodiment, Li3PS4 including a PS4 structure can also be used as a part of the raw material. Specifically, Li3PS4 and the like are prepared first and used as the raw material.

[0136] The content of Li3PS4 relative to the total of the raw materials is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 80 mol%.

[0137] In addition, when Li3PS4 and a halogen element are used, the content of the halogen element relative to Li3PS4 is preferably 1 to 50 mol%, more preferably 10 to 40 mol%, further preferably 20 to 30 mol%, and further preferably 22 to 28 mol%.

[0138] The lithium sulfide used in this embodiment is preferably in the form of particles.

[0139] The average particle size of lithium sulfide particles (D 50 ) is preferably 0.1 μm to 1000 μm, more preferably 0.5 μm to 100 μm, and even more preferably 1 μm to 20 μm. In this specification, the average particle size (D 50 ) is the particle size when the particle size distribution cumulative curve is drawn from the particle with the smallest particle size to 50% (volume basis) of the whole, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the raw materials exemplified as the above raw materials, the solid raw material preferably has an average particle size of the same degree as the above lithium sulfide particles. That is, it is preferably within the same range as the average particle size of the above lithium sulfide particles.

[0140] (About the blending ratio of raw materials)

[0141] In the manufacturing method of the present embodiment, the amount of elemental sulfur used exceeds 1.0 mole relative to 1.0 mole of lithium sulfide. By using elemental sulfur in excess like this, the generation of sulfur radicals is promoted, so the result is that a sulfide solid electrolyte with improved ion conductivity can be efficiently manufactured. From the viewpoint of more efficiently manufacturing a sulfide solid electrolyte with improved ion conductivity, the amount of elemental sulfur used is preferably 1.2 moles or more, more preferably 1.5 moles or more, and further preferably 1.7 moles or more. There is no particular restriction on the upper limit, but from the viewpoint of more efficiently obtaining a sulfide solid electrolyte, it is set to about 4.0 moles or less, preferably 3.0 moles or less.

[0142] In addition, the amount of elemental sulfur used is preferably 140% or more, more preferably 150% or more, further preferably 160% or more, and further preferably 170% or more relative to the sulfur atoms required to form the composition of the sulfide solid electrolyte to be obtained by the production method of the present embodiment. The upper limit is not particularly limited, but from the viewpoint of more efficiently obtaining the sulfide solid electrolyte, it may be about 300% or less, preferably 280% or less, more preferably 250% or less, and further preferably 230% or less.

[0143] When lithium sulfide, elemental sulfur, phosphorus pentasulfide and lithium halide are used as raw materials, from the viewpoint of obtaining higher chemical stability and higher ion conductivity, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is preferably 65 to 85 mol%, more preferably 70 to 82 mol%, and even more preferably 74 to 80 mol%.

[0144] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, lithium halide and other raw materials used as needed are used, the content of lithium sulfide and phosphorus pentasulfide relative to the total of these raw materials is preferably 50 to 99 mol%, more preferably 55 to 90 mol%, and even more preferably 60 to 85 mol%.

[0145] When lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 80 mol%, further preferably 35 to 80 mol%, and particularly preferably 45 to 70 mol%.

[0146] In addition, when lithium bromide and lithium chloride are used in combination as lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.

[0147] When a halogen element is used as a raw material and lithium sulfide, elemental sulfur, and phosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element to the total number of moles of lithium sulfide and phosphorus pentasulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen element is preferably in the range of 60 to 90%, more preferably in the range of 65 to 85%, further preferably in the range of 68 to 82%, further preferably in the range of 72 to 78%, and particularly preferably in the range of 73 to 77%. This is because these ratios can obtain higher ion conductivity.

[0148] Furthermore, from the same viewpoint, when lithium sulfide, elemental sulfur, phosphorus pentasulfide and a halogen element are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide and the halogen element is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, further preferably 3 to 25 mol%, and further preferably 3 to 15 mol%.

[0149] When lithium sulfide, elemental sulfur, phosphorus pentasulfide, a halogen element and a lithium halide are used, the content of the halogen element relative to the total amount of lithium sulfide, phosphorus pentasulfide, the halogen element and the lithium halide (α mol%) and the content of the lithium halide relative to the total amount of these (β mol%) preferably satisfy the following formula (2), more preferably satisfy the following formula (3), further preferably satisfy the following formula (4), and further preferably satisfy the following formula (5).

[0150] 2≤2α+β≤100…(2)

[0151] 4≤2α+β≤80…(3)

[0152] 6≤2α+β≤50…(4)

[0153] 6≤2α+β≤30…(5)

[0154] When two halogens are used as single substances, if the number of moles of one halogen atom in the substance is set to A1, and the number of moles of the other halogen atom in the substance is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 10:90 to 90:10, further preferably 20:80 to 80:20, and further preferably 30:70 to 70:30.

[0155] When two halogen elements are used and the two halogen elements are bromine and iodine, if the number of moles of bromine is set to A1 and the number of moles of iodine is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 20:80 to 80:20, further preferably 35:65 to 80:20, and further preferably 45:55 to 70:30.

[0156] Furthermore, when the two halogen elements are bromine and chlorine, if the number of moles of bromine is set to B1 and the number of moles of chlorine is set to B2, then B1:B2 is preferably 1:99 to 99:1, more preferably 15:85 to 75:25, further preferably 25:75 to 60:40, and further preferably 35:45 to 65:55.

[0157] (Solvent)

[0158] As the solvent used when mixing the above raw materials, an organic solvent is preferably used, and a solvent containing a heteroatom is preferably used. As the heteroatom contained in the solvent, oxygen atoms, nitrogen atoms, sulfur atoms, chlorine atoms, phosphorus atoms, etc. can be preferably exemplified, and oxygen atoms and nitrogen atoms are preferred. As the solvent containing a heteroatom, it can contain one of these heteroatoms, or it can contain multiple kinds.

[0159] As such a solvent containing heteroatoms, for example, there can be mentioned: solvents containing oxygen atoms such as alcohol solvents, ether solvents, ester solvents, aldehyde solvents, ketone solvents; solvents containing nitrogen atoms such as amine solvents and nitrile solvents; solvents containing oxygen atoms and nitrogen atoms such as amide solvents, etc. Among them, as solvents containing oxygen atoms, alcohol solvents and ether solvents are preferred, and as solvents containing nitrogen atoms, nitrile solvents are preferred. If these solvents are used, the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted, and a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.

[0160] These solvents can be used alone or in combination. Among the above, alcohol solvents are preferably included. By using alcohol solvents, the generation of sulfur free radicals and the promotion effect of the formation of electrolyte precursors (polysulfides) are particularly improved. In addition, in order to improve the promotion effect of the generation of sulfur free radicals and the formation of electrolyte precursors (polysulfides) in a balanced manner, it is preferred to use alcohol solvents in combination with other solvents.

[0161] As other solvents, it is preferred to use a solvent selected from a solvent having an oxygen atom other than an alcohol solvent and a solvent having a nitrogen atom, as a solvent having an oxygen atom other than an alcohol solvent, an ether solvent is preferred, and as a solvent having a nitrogen atom, a nitrile solvent is preferred. That is, the solvent preferably comprises an alcohol solvent and at least one organic solvent selected from an ether solvent and a nitrile solvent. It is particularly preferred to use an alcohol solvent, an ether solvent and a nitrile solvent in combination. Since the formation of sulfur free radicals and the formation of electrolyte precursors (polysulfides) are promoted in a well-balanced manner, a sulfide solid electrolyte with few impurities and high ionic conductivity can be efficiently obtained.

[0162] (Alcohol solvent)

[0163] Examples of the alcohol solvent include aliphatic alcohols, alicyclic alcohols, heterocyclic alcohols and aromatic alcohols. In view of availability and cost, aliphatic alcohols, alicyclic alcohols and aromatic alcohols are preferred, and aliphatic alcohols are more preferred.

[0164] As the aliphatic alcohol, for example, representative and preferred examples include: saturated or unsaturated monovalent aliphatic alcohols such as methanol, ethanol, various propanols, allyl alcohol, various butanols, and various butenols; saturated or unsaturated polyvalent aliphatic alcohols such as various propylene glycols, various propylene glycols, various butanediols, various butene glycols, various hexanediols, various hexene glycols, various butanetriols, erythritol, pentaerythritol, and dipentaerythritol.

[0165] In this specification, for example, in the case of various butanols, "various" means that all conceivable isomers such as 1-butanol, 2-butanol, 2-methyl-1-propanol, and 1,1-dimethylethanol are included. In addition, even if "various" is not marked, compounds described in a form without specifying the substitution position number also include all conceivable isomers.

[0166] The aliphatic hydrocarbon group in the aliphatic alcohol may be linear or branched, and may be saturated or unsaturated.

[0167] The carbon number of the aliphatic alcohol is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 12 or less, more preferably 8 or less, and further preferably 4 or less.

[0168] The aliphatic alcohol may be a partially substituted aliphatic alcohol, and preferred examples include alkanolamines partially substituted with amino groups such as ethanolamine, propanolamine, and dimethylethanolamine; and alcohols partially substituted with halogen atoms such as fluoroalcohols.

[0169] Representative examples of the alicyclic alcohol include: monovalent or polyvalent saturated or unsaturated monocyclic alicyclic alcohols such as cyclopropanol, methylcyclopropanol, cyclopropanemethanol, cyclobutanol, cyclobutenol, cyclopentanol, cyclopentenol, cyclohexanol, methylcyclohexanol, cyclohexenol, cyclohexanediol, and cyclohexanetriol; and monovalent or polycyclic alicyclic alcohols such as cyclopentylcyclopentanol, cyclohexylcyclohexanol, cyclohexylphenylcyclohexanol, and dicyclohexanol.

[0170] The carbon number of the alicyclic alcohol is preferably 3 or more, and the upper limit is preferably 12 or less, more preferably 10 or less, and further preferably 8 or less.

[0171] The alicyclic alcohol may be partially substituted, and preferably, alicyclic alcohols partially substituted with saturated or unsaturated hydrocarbon groups (including linear and branched hydrocarbon groups) such as alkyl and alkenyl groups, for example, alicyclic alcohols partially substituted with amino groups such as aminomethylcyclopropanol, and alicyclic alcohols partially substituted with halogen atoms, etc. In addition, alicyclic alcohols substituted with substituents such as amide groups and cyano groups may be mentioned.

[0172] Representative examples of the heterocyclic alcohol include monocyclic alcohols such as oxetane alcohol, oxetane methanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, tetrahydropyran methanol, morpholine alcohol, and pyridine methanol; and polycyclic condensed heterocyclic alcohols such as benzofuran methanol and dihydrobenzofuran methanol.

[0173] The number of carbon atoms in the heterocyclic alcohol is preferably 3 or more, and the upper limit is preferably 24 or less, more preferably 18 or less, and further preferably 12 or less.

[0174] The heterocyclic alcohol can be obtained by substituting a part of the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.

[0175] Representative and preferred examples of the aromatic alcohol include: monocyclic aromatic alcohols such as benzyl alcohol, salicyl alcohol, benzyl alcohol, methoxyphenyl alcohol, trimethoxyphenyl alcohol, and phenylethyl alcohol; polycyclic aromatic alcohols such as diphenyl alcohol and triphenyl alcohol; and condensed polycyclic aromatic alcohols such as naphthalene alcohol, anthracene alcohol, benzofuran alcohol, and dihydrobenzofuran alcohol.

[0176] The number of carbon atoms in the aromatic alcohol is preferably 7 or more, and the upper limit is preferably 24 or less, more preferably 20 or less, and further preferably 16 or less.

[0177] The aromatic alcohol can be obtained by partially substituting the alicyclic alcohol in the same manner as the above-mentioned alicyclic alcohol.

[0178] The above examples are merely representative examples of preferred alcohol solvents, and the solvents that can be used in the production method of the present embodiment are not limited to the above examples.

[0179] The alcohol solvent may be any of primary alcohol, secondary alcohol and tertiary alcohol, preferably primary alcohol. In addition, the alcohol solvent may be a monohydric alcohol having one hydroxyl group or a polyhydric alcohol having two or more hydroxyl groups, preferably a monohydric alcohol.

[0180] (Ether solvent)

[0181] Examples of the ether solvent include aliphatic ethers, alicyclic ethers, heterocyclic ethers and aromatic ethers. In view of availability and cost, aliphatic ethers, alicyclic ethers and aromatic ethers are preferred, aliphatic ethers and alicyclic ethers are more preferred, and alicyclic ethers are further preferred.

[0182] As the aliphatic ether, representative and preferred examples include: monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups such as diethylene glycol dimethyl ether (diglyme) and triethylene glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups such as diethylene glycol and triethylene glycol.

[0183] The carbon number of the aliphatic ether is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0184] Furthermore, the aliphatic alcohol may be linear or branched.

[0185] Representative examples of the alicyclic ethers include monocyclic alicyclic ethers such as ethylene oxide, propylene oxide, furan, tetrahydrofuran, pyran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, dioxene, dioxin, and dioxolane; and polycyclic alicyclic ethers such as dicyclopentyl ether and dicyclohexyl ether.

[0186] Typical examples of the heterocyclic ether include monocyclic heterocyclic ethers such as morpholine and hydroxymethyldimethoxypyridine; and polycyclic condensed heterocyclic ethers such as benzofuran, benzopyran, dibenzofuran and methoxyindole.

[0187] The carbon number of the alicyclic ether or heterocyclic ether is preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 10 or less.

[0188] In addition, typical and preferred examples of the aromatic ether include: monocyclic aromatic ethers such as methyl phenyl ether (anisole) and ethyl phenyl ether; polycyclic aromatic ethers such as dibenzyl ether, diphenyl ether and benzyl phenyl ether; and condensed polycyclic aromatic ethers such as benzylnaphthyl ether and bisnaphthyl ether.

[0189] The number of carbon atoms in the aromatic ether is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0190] The ether compound used in this embodiment may be an ether compound substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be either linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.

[0191] Among the above ether compounds, from the viewpoint of obtaining higher ion conductivity, alicyclic ethers are preferred, monocyclic alicyclic ethers are more preferred, and tetrahydrofuran is particularly preferred.

[0192] (Nitrile solvent)

[0193] Examples of the nitrile solvent include aliphatic nitrile, alicyclic nitrile, heterocyclic nitrile and aromatic nitrile. In view of availability and cost, aliphatic nitrile is preferred.

[0194] As the aliphatic nitriles, representative and preferred examples include: saturated or unsaturated aliphatic nitriles having one nitrile group, such as acetonitrile, acrylonitrile, methoxyacetonitrile, propionitrile, methoxypropionitrile, butyronitrile, etc.; saturated or unsaturated aliphatic nitriles having two or more nitrile groups, such as propane dinitrile, propane trinitrile, butane dinitrile, butene dinitrile, butane trinitrile, pentane dinitrile, pentane trinitrile, hexane dinitrile, hexene dinitrile, hexane trinitrile, methylene pentane dinitrile, etc.

[0195] The carbon number of the aliphatic nitrile is preferably 2 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 4 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic nitrile is preferably 1 or more, and the upper limit is preferably 8 or less, more preferably 6 or less, and further preferably 2 or less.

[0196] Furthermore, the aliphatic hydrocarbon group in the aliphatic nitrile may be linear or branched.

[0197] As the alicyclic nitriles, representative and preferred examples include: monocyclic or polycyclic alicyclic nitriles having one nitrile group, such as cyanocyclopropane, cyclobutanecarbonitrile, hydroxycyclobutanecarbonitrile, oxocyclobutanecarbonitrile, cyclopentanecarbonitrile, furancarbonitrile, tetrahydropyrancarbonitrile, cyclohexanecarbonitrile, and bicyclobutanecarbonitrile; and alicyclic nitriles having two or more nitrile groups, such as furan dicarbonitrile, cyclobutane dicarbonitrile, cyclopentane dicarbonitrile, cyclohexane dicarbonitrile, and cyclohexane tricarbonitrile.

[0198] As heterocyclic nitriles, representative and preferred examples include: monocyclic heterocyclic nitriles having one or more nitrile groups such as morpholinecarbonitrile, tetrahydrofuranonitrile, cyanopyridine, pyridinedicarbonitrile, pyridinetricarbonitrile, furfurylmalononitrile, etc.; polycyclic or polycyclic condensed heterocyclic nitriles having one or more nitrile groups such as benzofurancarbonitrile, dibenzofurandicarbonitrile, dicyanobipyridine, etc.

[0199] The carbon number of the alicyclic nitrile or heterocyclic nitrile is preferably 3 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 10 or less.

[0200] Representative examples of aromatic nitriles include monocyclic aromatic nitriles having one or more nitrile groups, such as benzyl cyanotoluene, benzonitrile, phthalonitrile, and benzene trimonitrile; and polycyclic or condensed polycyclic aromatic nitriles having one or more nitrile groups, such as biphenyl dicarbonitrile, phenylcyclobutane carbonitrile, naphthonitrile, naphthalenedicarbonitrile, naphthalene trimonitrile, anthracene carbonitrile, and cyclopentylbenzonitrile.

[0201] The number of carbon atoms in the aromatic nitrile is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0202] The ether compound used in this embodiment may be an ether compound substituted with a linear or branched hydrocarbon group such as an alkyl group or an alkenyl group, an alkoxy group (the alkyl group may be either linear or branched), a hydroxyl group, an amino group, an amide group, a cyano group or a halogen atom.

[0203] (Other solvents with heteroatoms)

[0204] In addition, regarding the amine solvents and amide solvents exemplified as solvents having heteroatoms other than the above-mentioned alcohol solvents, ether solvents, and nitrile solvents, for example, preferably exemplified are: heterocyclic aromatic amine solvents such as pyridine; amide solvents such as dimethylformamide, dimethylacetamide, hexamethylphosphoramide, N-methylpyrrolidone, etc.

[0205] (Other solvents)

[0206] In the manufacturing method of this embodiment, as a solvent, as other solvents other than the above-mentioned solvents, for example, aliphatic hydrocarbon solvents such as hexane, pentane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, and tert-butylbenzene can be used.

[0207] In this case, the less the usage amount of other solvents, the more preferred, for example, relative to 100.0 parts by volume of the above-mentioned solvent (i.e., the solvent comprising heteroatoms) usage amount is preferably below 50.0 parts by volume, more preferably below 30.0 parts by volume, and further preferably below 15.0 parts by volume. In addition, it is of course preferred not to use other solvents and only use the above-mentioned solvent (i.e., the solvent comprising heteroatoms).

[0208] (Amount of solvent used)

[0209] In the production method of this embodiment, when an alcohol solvent is used, the amount of the alcohol solvent used is preferably 0.005 mol or more, more preferably 0.010 mol or more, further preferably 0.015 mol or more, and further preferably 0.020 mol or more, relative to 1.0 mol of lithium sulfide used as a raw material. The upper limit is preferably 20.0 mol or less, more preferably 16.0 mol or less, and further preferably 10.0 mol or less.

[0210] In addition, when using at least one organic solvent selected from an alcohol solvent, an ether solvent and a nitrile solvent and an alcohol solvent is used, the total amount of the ether solvent and the nitrile solvent used is preferably 2.0 parts by volume or more, more preferably 5.0 parts by volume or more, further preferably 15.0 parts by volume or more, further preferably 50.0 parts by volume or more, and particularly preferably 150.0 parts by volume or more, and the upper limit is preferably 10000.0 parts by volume or less, more preferably 9000.0 parts by volume or less, further preferably 8000.0 parts by volume or less, and further preferably 7800.0 parts by volume or less.

[0211] (mix)

[0212] The manufacturing method of this embodiment mixes the raw material content containing the raw material in the above-mentioned solvent. By mixing the raw material content in the solvent, the generation of sulfur radicals and the formation of the electrolyte precursor are promoted, and a sulfide solid electrolyte with less impurities and high ion conductivity can be efficiently obtained.

[0213] There is no particular limitation on the method of mixing the raw material contents in the solvent, as long as the solvent and the raw material contents are put into a device capable of mixing the raw material contents in the solvent for mixing. For example, it is preferred to supply the solvent to the tank, operate the stirring blade, and then gradually add the raw material contents. In addition, it is also preferred to supply the raw material contents to the tank, operate the stirring blade, and then gradually add the solvent. Since a good mixing state of the raw material contents can be obtained, the dispersibility of the raw material is improved, and the generation of sulfur radicals and the formation of electrolyte precursors (polysulfides) are promoted.

[0214] However, when a halogen element is used as a raw material, the raw material is sometimes not solid. Specifically, at normal temperature and pressure, fluorine and chlorine become gases, and bromine becomes liquid. In such a case, for example, when the raw material is liquid, it can be supplied to the tank together with the solvent separately from other solid raw materials. In addition, when the raw material is gas, it can be supplied in a manner of blowing into a substance obtained by adding a solid raw material to a solvent.

[0215] The order in which the raw materials containing the raw materials are added and mixed is not particularly limited, but in consideration of work efficiency, all the raw materials are preferably added at the same time and mixed at once.

[0216] In addition, if considering improving the solubility of the raw materials, further suppressing the generation of impurities, and more efficiently obtaining a sulfide solid electrolyte with high ion conductivity, it is preferred to divide the raw materials into two raw material groups, raw material group 1 and raw material group 2, and mix them in batches by mixing raw material group 1 and then raw material group 2.

[0217] When batch mixing is performed, as described above, the raw material group 1 preferably contains elemental sulfur. This promotes the formation of sulfur radicals and allows a sulfide solid electrolyte having high ion conductivity to be obtained more efficiently.

[0218] From the same viewpoint, as described above, the combination of raw material group 1 and raw material group 2 is preferred, wherein raw material group 1 includes a raw material including at least one atom selected from lithium atoms, phosphorus atoms, and sulfur atoms, and elemental sulfur and lithium sulfide, and raw material group 2 includes a raw material including a halogen atom. This is because the raw material group 1 includes elemental sulfur and lithium sulfide, and the reaction of these elements promotes the formation of sulfur radicals through lithium polysulfide. From the same viewpoint, the combination of raw material group 1 and raw material group 2 is also preferred, wherein raw material group 1 includes a raw material including a halogen atom, elemental sulfur, and lithium sulfide, and raw material group 2 includes a raw material including a phosphorus atom and a sulfur atom.

[0219] In the production method of the present embodiment, the order of charging and mixing the raw materials may be selected according to whether priority is given to work efficiency or to the ion conductivity of the sulfide solid electrolyte.

[0220] In addition, as described above, in the manufacturing method of the present embodiment, as a raw material included in the raw material content, Li3PS4 or the like containing a PS4 structure can be prepared and used. Li3PS4 can be manufactured by, for example, mixing lithium sulfide and phosphorus pentasulfide at a molar ratio of 75:25, respectively. In the manufacturing method of the present embodiment, when phosphorus pentasulfide is used as a raw material in addition to lithium sulfide, a raw material group containing lithium sulfide and phosphorus pentasulfide and elemental sulfur at a specified molar ratio of 75:25 or the like can be mixed in a solvent as raw material group 1, and then a raw material containing halogen atoms such as lithium halide, other remaining raw materials required for manufacturing the desired sulfide solid electrolyte, such as a raw material group containing the insufficient part of lithium sulfide, is added as raw material group 2 and mixed. By pre-forming an electrolyte precursor (polysulfide) containing the basic structure of Li3PS4, a sulfide solid electrolyte can be obtained more efficiently.

[0221] Here, the predetermined molar ratio of the lithium sulfide to the phosphorus pentasulfide is preferably 55 to 85:15 to 45, more preferably 60 to 80:20 to 40, and even more preferably 65 to 75:25 to 35.

[0222] The manufacturing method of the present embodiment is characterized in that it includes: mixing the raw material content in the solvent. That is, the raw material content only needs to be mixed without crushing, so it is possible to manufacture by a method that does not use a device generally referred to as a crusher, such as a media crusher such as a ball mill or a bead mill, which is used for the purpose of crushing the solid electrolyte raw material. In the manufacturing method of the present embodiment, the solvent and the raw material can be mixed only by simply mixing the raw material content in the solvent to generate a polysulfide as an electrolyte precursor, and by decomposing it by heating or the like, an amorphous sulfide solid electrolyte can be formed, and then a crystalline sulfide solid electrolyte can be formed.

[0223] In order to shorten the mixing time for obtaining the electrolyte precursor or to pulverize the mixture of the raw materials in the solvent, a pulverizer may be used to pulverize the mixture. However, as described above, it is preferred not to use a pulverizer.

[0224] As a device for mixing the raw material content in the solvent, for example, a mechanical stirring mixer with stirring blades in a tank can be cited. The mechanical stirring mixer can be exemplified by a high-speed stirring mixer, a double-arm mixer, etc., and from the viewpoint of improving the uniformity of the raw materials in the mixture of the raw material content and obtaining higher ion conductivity, a high-speed stirring mixer is preferably used. In addition, as a high-speed stirring mixer, a vertical axis rotating mixer, a horizontal axis rotating mixer, etc. can be cited, and any type of mixer can also be used.

[0225] As the shape of the stirring blade used in the mechanical stirring mixer, anchor type, blade type, arm type, belt type, multi-stage blade type, two-arm type, bucket type, biaxial blade type, flat blade type, C-type blade type etc. can be exemplified, from the viewpoint of improving the uniformity of solid electrolyte raw materials, obtaining higher ionic conductivity, preferably use bucket type, flat blade type, C-type blade type. In addition, in the mechanical stirring mixer, preferably set the circulation line that returns to the inside of the mixer again after the stirring object is discharged to the outside of the mixer. Thus, the raw materials with heavier specific gravity such as lithium halides will not precipitate and will not be stirred by retention, and more uniform mixing can be carried out.

[0226] Although the location of the circulation line is not particularly limited, it is preferably located at a location where the liquid is discharged from the bottom of the mixer and returned to the upper part of the mixer. Thus, the solid electrolyte raw material that is easy to precipitate is easily stirred evenly with the convection of the circulation. Furthermore, the return port is preferably located below the liquid surface of the stirring object. Thus, it is possible to suppress liquid splashing and cause the stirring object to adhere to the wall surface inside the mixer.

[0227] There is no particular upper limit to the mixing time when mixing the raw material content in the solvent. Taking efficiency into consideration, it is preferably 240 minutes or less, more preferably 60 minutes or less, further preferably 30 minutes or less, and further preferably 15 minutes or less. The lower limit is usually 0.1 minutes or more, preferably 1 minute or more, and further preferably 3 minutes or more.

[0228] The temperature conditions for mixing the raw material content in the solvent are not particularly limited, but are, for example, -30 to 100°C, preferably -10 to 50°C, and more preferably about room temperature (23°C) (eg, about room temperature ±5°C).

[0229] 〔heating〕

[0230] The production method of this embodiment includes: heating after mixing the raw material content. By heating, the generated polysulfide can be decomposed, the solvent can be removed, and the elemental sulfur generated by the decomposition of the polysulfide can be removed and crystallized. In addition, although the elemental sulfur can be removed by heating, a different method such as solvent washing and hydrodesulfurization can be used for the removal of the elemental sulfur.

[0231] The heating temperature is not particularly limited as long as it is room temperature or higher, and the room temperature may vary, so it cannot be generalized, but it is usually preferably 20° C. or higher, and the upper limit is preferably 500° C. or lower. When the heating temperature is within the above range, decomposition of polysulfides, removal of solvents, and removal of elemental sulfur can be performed more efficiently, and crystallization can be performed.

[0232] Furthermore, when heating, it is preferable to perform heating in multiple stages. For example, it is preferable to perform heating (first heating) mainly for decomposing the generated polysulfide, removing the solvent and removing the elemental sulfur, and then perform heating (second heating) for crystallization. More specifically, it is preferable to perform first heating at a heating temperature of 20°C or higher and lower than 150°C and second heating at a heating temperature of 150°C or higher and 500°C or lower.

[0233] The heating temperature in the first heating may be 20° C. or higher and lower than 150° C. For example, the first heating may be performed by heating at a lower temperature and then heating at a higher temperature, that is, by performing heating in multiple stages.

[0234] Generally, the removal of the solvent starts at 20°C or higher, the decomposition of the polysulfide starts at 60°C or higher, and the removal of sulfur starts at 100°C or higher. By performing multi-stage heating at heating temperatures corresponding to these purposes, each purpose can be more efficiently achieved, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity. In particular, with respect to the removal of elemental sulfur, by reliably performing this removal, the generation of impurities caused by the residual elemental sulfur can be further suppressed, so it is easy to obtain a sulfide solid electrolyte with improved ion conductivity.

[0235] For example, the heating temperature when heating at a lower temperature (first heating-1) is preferably 20° C. or higher, and the upper limit is preferably lower than 60° C., more preferably 50° C. or lower. By setting the temperature in such a range, the solvent can be removed.

[0236] Next, the heating temperature when heating at a higher temperature (first heating-2) is preferably 60° C. or higher, more preferably 65° C. or higher, further preferably 75° C. or higher, further preferably 95° C. or higher, and particularly preferably 110° C. or higher, and the upper limit is lower than 150° C., more preferably 145° C. or lower, further preferably 135° C. or lower, and further preferably 130° C. or lower. By setting the temperature in such a range, decomposition of polysulfides and removal of sulfur can be mainly performed.

[0237] As described above, the first heating can remove the solvent, decompose the polysulfide, and remove the sulfur depending on the heating temperature, so various methods can be adopted by adjusting the heating temperature. For example, if the heating temperature of the first heating is set to 60°C or more (lower than 100°C), the solvent can be removed and the polysulfide can be decomposed, so it is set as the first heating-1, and the sulfur can be removed by heating at 100°C or more (lower than 150°C) as the first heating-2. In this case, the first heating-2 can be omitted, and the sulfur can be removed by a method other than heating, that is, solvent washing, hydrodesulfurization, etc., as described above, and then the second heating can be performed. In addition, the method of solvent washing, hydrodesulfurization, etc. for removing sulfur will be described later.

[0238] In addition, for example, the following three-stage heating can be performed: if the heating temperature of the first heating is set to 20°C or higher (lower than 60°C), the solvent can be removed, so it is set as the first heating-1, if it is heated at 60°C or higher (lower than 100°C) as the first heating-2, polysulfide can be decomposed, and further, it is heated at 100°C or higher (lower than 150°C) as the first heating-3 to remove sulfur. In this case, it is also possible to remove sulfur by a method other than heating as described above instead of the first heating-3, and by setting the heating temperature of the first heating-2 to 100°C or higher (lower than 150°C), it is also possible to decompose polysulfide and remove sulfur at the same time.

[0239] In the above, the case where the first heating is performed by multi-stage heating is described. However, if the heating temperature of the first heating is set to 100° C. or higher, for example, the solvent can be removed, polysulfide can be decomposed, and sulfur can be removed. Therefore, multi-stage heating may not be performed.

[0240] The heating time of the first heating is not particularly limited as long as it is the time of the degree that can remove the solvent at least, for example, is preferably more than 10 minutes, more preferably more than 30 minutes, more preferably more than 45 minutes, and more preferably more than 1 hour. In addition, the upper limit of the heating time is not particularly limited, and is preferably less than 24 hours, more preferably less than 10 hours, more preferably less than 5 hours, and more preferably less than 3 hours.

[0241] The pressure condition during the first heating is preferably set to normal pressure or reduced pressure. When set to reduced pressure, specifically, it is preferably below 85 kPa, more preferably below 80 kPa, and further preferably below 70 kPa. The lower limit may be vacuum (0 kPa). Considering the ease of adjusting the pressure, it is preferably above 1 kPa, more preferably above 2 kPa, and further preferably above 3 kPa.

[0242] In addition, the heating is preferably performed in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or in a reduced pressure atmosphere (particularly in a vacuum). For example, an inert gas atmosphere containing a certain concentration of hydrogen may also be used. This is because the degradation (e.g., oxidation) of the sulfide solid electrolyte can be prevented.

[0243] The heating temperature in the second heating cannot be generalized because it can be changed depending on the sulfide solid electrolyte to be produced. However, considering the relationship with the first heating, it can be 150°C to 500°C, preferably 160°C or more, more preferably 200°C or more, and further preferably 240°C or more. The upper limit is preferably 480°C or less, more preferably 460°C or less, and further preferably 440°C or less.

[0244] The second heating may be performed in multiple stages as in the first heating. By performing multiple stages of heating as the second heating, more reliable crystallization can be achieved.

[0245] In the case of multi-stage heating, for example, the heating temperature when heating at a lower heating temperature (second heating-1) is set to 150°C or more and less than 270°C, and the heating temperature when heating at a higher heating temperature (second heating-2) is set to 270°C or more and 500°C or less. As the lower limit of the second heating-1, it is preferably set to the temperature of the lower limit of the second heating, and as the upper limit, it is preferably 265°C or less, and more preferably 255°C or less. In addition, as the upper limit of the second heating-2, it is preferably set to the temperature of the upper limit of the second heating, and as the lower limit, it is preferably 290°C or more, more preferably 340°C or more, and further preferably 375°C or more.

[0246] The heating time and pressure conditions in the second heating are the same as those in the first heating, and the heating time and pressure conditions are also the same in that the second heating is preferably performed in an inert gas atmosphere.

[0247] The heating method is not particularly limited, and examples thereof include methods using various heating devices such as a hot plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, and a vacuum firing furnace. In addition, in industry, a horizontal dryer or a horizontal vibrating fluidized dryer having a heating unit and a feeding mechanism can also be used, and the method can be selected according to the amount of heating treatment.

[0248] (Sulfur Removal)

[0249] In the production method of this embodiment, sulfur removal may be performed by a method other than heating as described above. For example, when the first heating temperature is set to be lower than 100° C., sulfur removal is preferably performed by a method other than heating. Examples of the method for removing sulfur include solvent washing and hydrodesulfurization.

[0250] The method of washing with a solvent includes, for example, washing the first heated powder with a solvent that dissolves sulfur, such as an aromatic hydrocarbon solvent such as benzene, toluene, or xylene; or a sulfur-containing organic solvent such as carbon disulfide, to remove sulfur.

[0251] As a method utilizing hydrodesulfurization, the powder subjected to the first heating is mixed with a hydrodesulfurization catalyst, and hydrogen is passed through the mixture while heating at 300 to 450° C., thereby removing sulfur by a hydrodesulfurization reaction. Here, as the hydrodesulfurization catalyst, preferably, a porous catalyst containing nickel, molybdenum, cobalt, tungsten, or the like as an active metal element, such as a NiMo catalyst, a CoMo catalyst, or a NiW catalyst, can be cited.

[0252] (Amorphous sulfide solid electrolyte)

[0253] In the production method of the present embodiment, an amorphous sulfide solid electrolyte is produced by mixing the raw material contents or performing the first heating mainly for removing the solvent.

[0254] The amorphous sulfide solid electrolyte generated in the manufacturing method of this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc., can be preferably cited; solid electrolytes containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc. are preferred.

[0255] The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0256] In the case where the amorphous sulfide solid electrolyte generated in the manufacturing method of this embodiment has at least Li2S-P2S5, from the viewpoint of obtaining higher ion conductivity, the molar ratio of Li2S to P2S5 is preferably 65 to 85:15 to 35, more preferably 70 to 82:18 to 30, and further preferably 74 to 80:20 to 26.

[0257] For example, when the amorphous sulfide solid electrolyte generated in the manufacturing method of the present embodiment is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 75 mol%, and particularly preferably 45 to 60 mol%.

[0258] In addition, for example, when the amorphous sulfide solid electrolyte generated in the manufacturing method of the present embodiment is Li2S-P2S5-LiCl-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 45 to 80 mol%, more preferably 50 to 75 mol%, and further preferably 55 to 70 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.

[0259] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.

[0260] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 200.0 μm or less, further 100.0 μm or less, 10.0 μm or less, 1.0 μm or less, 0.5 μm or less.

[0261] (Crystalline sulfide solid electrolyte)

[0262] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte to a temperature higher than the crystallization temperature, and its crystal structure can be exemplified by Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0263] Another example is Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P xS4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). From the perspective of obtaining higher ionic conductivity, the crystal structure of the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is preferably a thio-LISICON Region II type crystal structure among the above. Here, "thio-LISICON Region II type crystal structure" means Li 4-x Ge 1-x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.

[0264] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment may be a crystalline sulfide solid electrolyte containing the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure, or may be a crystalline sulfide solid electrolyte containing the sulfide crystallized lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred that the sulfide crystallized lithium superion conductor region type II crystal structure be contained as a main crystal. In this specification, "containing as a main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).

[0265] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge1-x P x Diffraction peaks of the crystal structure of the thio-LISICON Region II type of S4-class sulfide crystalline lithium superionic conductor appear near 2θ = 20.1°, 23.9°, 29.5°, etc., and are related to Li 4-x Ge 1-x P x Diffraction peaks of a crystal structure similar to the thio-LISICON Region II type of S4-class sulfide crystalline lithium superionic conductor appear near 2θ = 20.2°, 23.6°, etc. Additionally, these peak positions can fluctuate within a range of ±0.5°.

[0266] Crystalline sulfide solid electrolytes having the following crystal structures can also be preferably exemplified: having the structural framework of the above-mentioned Li7PS6 and a thiogermanate-type crystal structure in which a part of P is replaced by Si.

[0267] As a compositional formula of the thiogermanate-type crystal structure, for example, a crystal structure represented by the compositional formula Li 7-x P 1-y Si y S6 and Li 7+x P 1- y Si y S6 (where x is -0.6 to 0.6 and y is 0.1 to 0.6) can be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0268] As a compositional formula of the thiogermanate-type crystal structure, a compositional formula Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) can also be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0269] In addition, as a compositional formula of the thiogermanate-type crystal structure, a compositional formula Li 7-x PS 6-x Ha x(Ha is Cl or Br, and x is preferably 0.2 to 1.8.) The argyrodite-type crystal structure represented by the composition formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it mainly has peaks appearing at positions of 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0270] In addition, these peak positions can float within a range of ±0.5°.

[0271] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.

[0272] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 200.0 μm or less, further 100.0 μm or less, 10.0 μm or less, 1.0 μm or less, 0.5 μm or less.

[0273] (use)

[0274] The sulfide solid electrolyte obtained by the production method of the present embodiment has high ion conductivity and excellent battery performance, and therefore is suitable for use in batteries.

[0275] The sulfide solid electrolyte obtained by the production method of this embodiment can be used for the positive electrode layer, the negative electrode layer, or the electrolyte layer. In addition, each layer can be produced by a known method.

[0276] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the solid electrolyte such as Au, Pt, Al, Ti or Cu can be used.

[0277] Example

[0278] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.

[0279] (Measurement of powder XRD diffraction)

[0280] Powder X-ray diffraction (XRD) measurements were performed as follows.

[0281] The powder of the sulfide solid electrolyte obtained in the examples and comparative examples was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and flattened with glass to prepare a sample. The sample was sealed with a kapton film for XRD and measured under the following conditions in a manner that it was not in contact with air.

[0282] Measuring device: D2 PHASER, manufactured by Bruker Corporation

[0283] Tube voltage: 30kV

[0284] Tube current: 10mA

[0285] X-ray wavelength: Cu-Kα ray

[0286] Optical system: Concentration method

[0287] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (Ni plate)

[0288] Detector: Semiconductor detector

[0289] Measuring range: 2θ = 10-60 degrees

[0290] Step width, scanning speed: 0.05deg, 0.05deg / second

[0291] (Measurement of ionic conductivity)

[0292] In this example, the measurement of ion conductivity was performed as follows.

[0293] The crystalline sulfide solid electrolytes obtained in the examples and comparative examples were formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0294] R=ρ(L / S)

[0295] σ=1 / ρ

[0296] (Example 1)

[0297] In a glove box under an argon atmosphere, 0.2546 g of lithium sulfide, 0.3241 g of phosphorus pentasulfide and 0.3554 g of elemental sulfur were mixed using a mortar and introduced into a 100 ml reaction tank (reaction tank 1) together with a stirrer. Similarly, 0.1236 g of lithium chloride and 0.1520 g of lithium bromide were mixed using a mortar and introduced into a 100 ml reaction tank (reaction tank 2) different from the above together with a stirrer. Under a nitrogen atmosphere, 60 mL of a mixed solvent of ethanol (EtOH), tetrahydrofuran (THF) and acetonitrile (ACN) (the total amount of tetrahydrofuran (THF) and acetonitrile (ACN) was 40.1 parts by volume relative to 1.0 parts by volume of ethanol (EtOH), ethanol:tetrahydrofuran:acetonitrile = 0.050:1:1 (volume ratio)) was added to reaction tank 1, and the mixture was stirred for 10 minutes with a magnetic stirrer for mixing. Next, the solution in reaction tank 1 was added to reaction tank 2, and the mixture was further stirred and mixed for 10 minutes using a magnetic stirrer.

[0298] Then, using a vacuum pump and an oil bath, heating was performed at room temperature (20°C) under reduced pressure for 1 hour (first heating-1), and heating was performed at 130°C under reduced pressure for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated at 250°C in an argon atmosphere for 1 hour (second heating-1), and further heated at 430°C in a nitrogen atmosphere for 8 hours (second heating-2) to obtain a powder.

[0299] Powder XRD diffraction was measured for the powders obtained at room temperature (20°C) and 130°C in the first heating and at 250°C and 430°C in the second heating. The X-ray diffraction spectrum of the powder obtained by heating at 130°C is shown in FIG. Figure 1 and 4 The X-ray diffraction spectrum of the powder obtained by heating at 250°C is shown in Figure 2 and 5 The X-ray diffraction spectrum of the powder obtained by heating at 430°C is shown in Figure 3 and 6 .

[0300] Furthermore, the ion conductivity of the powder obtained by heating at 430° C. in Example 1 was measured and found to be 4.8 mS / cm.

[0301] (Examples 2, 3, 4 and 7)

[0302] Powders of Examples 2, 3, 4 and 7 were obtained in the same manner as in Example 1, except that the composition ratio and supply amount of the solvent were set to the conditions shown in Table 1A.

[0303] Powder XRD diffraction was measured for the powders obtained in Examples 2, 3, 4 and 7. The X-ray diffraction spectra of the powders obtained by heating at 130° C. in Examples 2, 3 and 4 are shown in FIG. Figure 1 The X-ray diffraction spectra of the powders obtained by heating at 250° C. in Examples 2, 3 and 4 are shown in Figure 2 The X-ray diffraction spectra of the powders obtained by heating at 430° C. in Examples 2, 3 and 4 are shown in Figure 3 The X-ray diffraction spectra of the powders obtained by heating at 130°C, 250°C and 430°C in Examples 2 and 7 are shown in Fig.10 , 11 and 12.

[0304] In addition, the ion conductivity was measured for the powders obtained by heating at 430° C. in Examples 2, 3, 4, and 7. The results are shown in Table 1A.

[0305] (Example 5)

[0306] A powder was obtained in the same manner as in Example 2, except that all the raw materials were mixed in a mortar at the same time, introduced into the reaction tank, and stirred and mixed with the solvent for 10 minutes.

[0307] (Example 6)

[0308] A powder was obtained in the same manner as in Example 2, except that in Example 2, 0.1236 g of lithium chloride, 0.1520 g of lithium bromide, 0.2546 g of lithium sulfide and 0.3554 g of sulfur were introduced into the reaction tank and stirred and mixed with the solvent for 10 minutes (reaction tank 1), and then the solution in reaction tank 1 was added to reaction tank 2 into which 0.3241 g of phosphorus pentasulfide was introduced, and stirred and mixed for 10 minutes.

[0309] The X-ray diffraction spectra of the powders obtained by heating at 130° C. in Examples 2, 5 and 6 are shown in FIG. Figure 7 The X-ray diffraction spectra of the powders obtained by heating at 250° C. in Examples 2, 5 and 6 are shown in Figure 8 The X-ray diffraction spectra of the powders obtained by heating at 430° C. in Examples 2, 5 and 6 are shown in Fig. 9 In addition, the ion conductivity of the powders obtained by heating at 430° C. in Examples 5 and 6 was measured. The results are shown in Table 1A.

[0310] (Comparative Examples 1 and 2)

[0311] Powders of Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the amount of sulfur used was changed from 0.3544 g to 0.1269 g and 0.1777 g, respectively.

[0312] The X-ray diffraction spectra of the powders obtained by heating at 130° C. in Comparative Examples 1 and 2 are shown in FIG. Figure 4 The X-ray diffraction spectra of the powders obtained by heating at 250° C. in Comparative Examples 1 and 2 are shown in Figure 5 The X-ray diffraction spectra of the powders obtained by heating at 430° C. in Comparative Examples 1 and 2 are shown in Figure 6 In addition, the ion conductivity of the powders obtained by heating at 430° C. in Comparative Examples 1 and 2 was measured. The results are shown in Table 1A.

[0313] [Table 1]

[0314] Table 1A

[0315]

[0316] *1. Raw material supply methods A to C are as follows.

[0317] A: After mixing lithium sulfide, phosphorus pentasulfide and elemental sulfur, mix lithium chloride and lithium bromide.

[0318] B: Mix lithium sulfide, phosphorus pentasulfide, elemental sulfur, lithium chloride and lithium bromide at the same time.

[0319] C: After mixing lithium chloride, lithium bromide, lithium sulfide and elemental sulfur, phosphorus pentasulfide is mixed.

[0320] (Examples 8 to 11)

[0321] The powder of Example 8 was obtained in the same manner as in Example 1, except that the amount of sulfur atoms used, the composition ratio and the supply amount of the solvent were set to the conditions shown in Table 1B in Example 1. In addition, the powders of Examples 9 to 11 were obtained in the same manner as in Example 1, except that the composition ratio and the supply amount of the solvent were set to the conditions shown in Table 1B in Example 1.

[0322] The powders obtained in Examples 8 to 11 were subjected to powder XRD diffraction measurement. The X-ray diffraction spectra of the powders obtained by heating at 130°C, 250°C and 430°C in Example 8 are shown in FIG. Figures 15 to 17 (The X-ray diffraction spectra in these figures also include those of Example 1 and Comparative Examples 1 and 2.) The X-ray diffraction spectra of the powders obtained by heating at 130°C, 250°C and 430°C in Examples 9 to 11 are shown in FIG. Figures 18 to 20 (The X-ray diffraction spectra in these figures also include those of Example 2.) In addition, the ion conductivity of the powders obtained by heating at 430° C. in Examples 8 to 11 was measured. The results are shown in Table 1B.

[0323] [Table 2]

[0324] Table 1B

[0325]

[0326] like Figure 2 , 3 , 5, 6, 8, 9, 11 and 12, the powders obtained by heating at 250°C and 430°C of Examples 1 to 7 have peaks at 2θ=15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0° and 52.0°, and thus are confirmed to be crystalline sulfide solid electrolytes having an argyrodite type crystal structure. In addition, as Fig.16 , 17 , 19 and 20, it was confirmed that the powders obtained by heating at 250°C and 430°C in Examples 8 to 11 were crystalline sulfide solid electrolytes having an argyrodite-type crystal structure, similarly to Examples 1 to 7.

[0327] For the powders obtained by heating at 130° C. in Examples 1 to 7 and the powders obtained by heating at 130° C. in Examples 8 to 11, Figure 1 , 4 , 7 and 10, and Fig.15 and 18 As shown, although some impurity peaks were observed, the peaks due to the argyrodite type crystal structure were confirmed, confirming that it was a crystalline sulfide solid electrolyte having the argyrodite type crystal structure. In Examples 5 and 6, a peak believed to be caused by lithium sulfide was confirmed at 2θ=27.0°, and in Examples 1, 2, 5, 6, and 7, a peak believed to be caused by lithium chloride was confirmed at 2θ=34.9°. In addition, it can be seen that the peak intensity due to the argyrodite type crystal structure is weaker than the peak intensity of the crystalline sulfide solid electrolyte after heating at 250°C and 430°C. According to Figure 3 , 6 , 9 and 12 and Figure 1 , 4 , 7 and 10, it was confirmed that by heating at a higher temperature (equivalent to the second heating), the peaks caused by raw materials such as lithium sulfide and lithium chloride could no longer be confirmed, and the degree of crystallinity was improved.

[0328] like Figure 3As shown, the powders obtained by heating at 430°C in Examples 3 and 4 have smaller peak intensities at 2θ=22.1° and 23.0° derived from P2O5, and larger peak intensities due to the argyrodite type crystal structure, compared with the powders of Examples 1 and 2. It is believed that by reducing the amount of alcohol solvent (ethanol) in the solvent, the generation of oxides of oxygen derived from ethanol is suppressed, and the crystallinity of the crystalline sulfide solid electrolyte having the argyrodite type crystal structure is improved. The ion conductivities of the powders of Examples 1, 2, 3, and 4 are 4.8 mS / cm, 5.3 mS / cm, 6.7 mS / cm, and 8.4 mS / cm, respectively. The smaller the amount of ethanol in the solvent and the smaller the amount of alcohol solvent (ethanol) used relative to lithium sulfide, the higher the conductivity.

[0329] like Figure 7 As shown in the figure, in the powders obtained by heating at 130°C in Examples 2, 5 and 6, a peak considered to be caused by lithium sulfide was confirmed at 2θ=27.0° only in Examples 5 and 6. This shows that a crystalline sulfide solid electrolyte having an argyrodite-type crystal structure can be obtained regardless of the method of supplying the raw material, but supply method A allows the reaction to proceed most efficiently. Fig. 9 As shown, in the powders obtained by heating at 430°C in Examples 5 and 6 other than the supply method A, the peak due to lithium sulfide disappeared due to the reaction proceeding by heating. However, for example, the ion conductivities of the powders of Examples 2, 5, and 6 were 5.3 mS / cm, 4.3 mS / cm, and 4.3 mS / cm, respectively, and it can be seen that the supply method A can obtain the highest ion conductivity.

[0330] Based on the above results, it was confirmed that, although a sulfide solid electrolyte having sufficiently high ion conductivity can be obtained regardless of the supply method, in order to obtain higher ion conductivity, batch supply in which the raw materials are supplied in raw material groups 1 and 2, and in particular, supply in which the raw material groups 1 and 2 are separated into the following raw material groups 1 and 2 are effective, compared with mixing the raw materials all at once: Raw material group 1 contains: a raw material containing at least one atom selected from lithium atoms, phosphorus atoms and sulfur atoms, and elemental sulfur and lithium sulfide; Raw material group 2 contains: a raw material containing halogen atoms.

[0331] The powders obtained by heating at 130°C and 250°C in Comparative Examples 1 and 2 are as follows: Figure 4 and 5 As shown in FIG. 1 , similarly to the powder of Example 1, a peak due to the argyrodite crystal structure was also confirmed, but a large peak due to lithium sulfide was also confirmed at 2θ=27.0°, indicating that the reaction did not proceed efficiently. Figure 6As shown, in the powders obtained by heating at 430° C. in Comparative Examples 1 and 2, the peak due to lithium sulfide disappears due to the reaction caused by heating. However, for example, the ion conductivities of the powders of Example 1, Comparative Examples 1 and 2 are 4.8 mS / cm, 3.5 mS / cm and 3.6 mS / cm, respectively, which are lower than that of the powder of Example 1. In addition, Example 8 is an example in which 1.5 moles of sulfur atoms are used relative to 1.0 mole of lithium sulfide, and the ion conductivity is 3.8 mS / cm. Therefore, it is confirmed that a higher ion conductivity can be obtained than the ion conductivity of the powder of the Comparative Example, similarly to the example in which 2.0 moles are used. As described above, the powder of Example 8 confirms a peak due to the argyrodite type crystal structure similarly to Example 1, and it is considered that the powder of Example 8 has a high ion conductivity by using more than 1.0 mole of elemental sulfur as sulfur atoms relative to 1.0 mole of lithium sulfide.

[0332] From the above results, it was confirmed that by using an excessive amount of elemental sulfur, sulfur radicals were generated via lithium polysulfide, thereby generating soluble polysulfide (i.e., electrolyte precursor) caused by the reaction of all raw materials, and as a result, a sulfide solid electrolyte with improved ion conductivity was obtained. On the other hand, in Comparative Examples 1 and 2, although the peak due to lithium sulfide disappeared, the reaction of all raw materials did not proceed well, and thus the composition as a sulfide solid electrolyte was not fully formed, and it was confirmed that high ion conductivity could not be obtained.

[0333] like Fig.10 , 11 As shown in Figures 1 and 2, no significant difference was found between the powders obtained by heating at 130°C, 250°C and 430°C in Examples 2 and 7, so it can be seen that even if the amount of solvent used is changed while maintaining the amount of ethanol, it will not have a significant effect on the obtained powder. Regarding the ion conductivity, the ion conductivity of the powders of Examples 2 and 7 was 5.3 mS / cm and 4.5 mS / cm, respectively, and the same values ​​were obtained. From the above results, it can be seen that among alcohol solvents, ether solvents and nitrile solvents that are solvents having heteroatoms such as oxygen atoms and nitrogen atoms, it is particularly effective to maintain the amount of alcohol solvent.

[0334] According to Examples 9 and 11, it was confirmed that a crystalline sulfide solid electrolyte having an argyrodite type crystal structure can be obtained even without using an alcohol solvent, an ether solvent, and a nitrile solvent in combination as a solvent when mixing the raw material content as in Examples 1 to 8.

[0335] Furthermore, it can be seen from Examples 9 to 11 that when an alcohol solvent is used as a solvent, the amount of the alcohol solvent used can be widely adopted, and when an ether solvent and a nitrile solvent are used, the ratio of these solvents is not limited to one ratio but can be widely adopted.

[0336] (Example 12)

[0337] In a glove box under a nitrogen atmosphere, 0.2590 g of lithium sulfide, 0.4177 g of phosphorus pentasulfide and 0.3616 g of elemental sulfur were mixed using a mortar and introduced into a 100 ml reaction tank (reaction tank 1) together with a stirrer. Similarly, 0.1776 g of lithium iodide was weighed and introduced into a 100 ml reaction tank (reaction tank 2) different from the above together with a stirrer. Under a nitrogen atmosphere, 32.62 mL of a mixed solvent of ethanol (EtOH), tetrahydrofuran (THF) and acetonitrile (ACN) (the total amount of tetrahydrofuran (THF) and acetonitrile (ACN) was 512.7 parts by volume relative to 1.0 parts by volume of ethanol (EtOH), ethanol:tetrahydrofuran:acetonitrile = 0.0039:1:1 (volume ratio)) was added to reaction tank 1, and the mixture was stirred for 10 minutes using a magnetic stirrer for mixing. Next, the solution in reaction tank 1 was added to reaction tank 2, and the mixture was further stirred and mixed for 10 minutes using a magnetic stirrer.

[0338] Then, using a vacuum pump and an oil bath, heating was performed under reduced pressure at room temperature (20°C) for 1 hour (first heating-1), and heating was performed under reduced pressure at 130°C for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated under reduced pressure at 170°C for 2 hours (second heating-1) to obtain a powder.

[0339] The powder obtained by heating at 130°C in the first heating and at 170°C in the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum of the powder obtained by heating at 130°C is shown in FIG. Fig.13 and 21 The X-ray diffraction spectrum of the powder obtained by heating at 170°C is shown in Fig.14 and 22 .

[0340] (Example 13)

[0341] In a glove box under a nitrogen atmosphere, 0.6294 g of lithium sulfide, 1.0149 g of phosphorus pentasulfide, 0.6589 g of elemental sulfur, 0.1400 g of lithium bromide and 0.2157 g of lithium iodide were mixed using a mortar and introduced into a 100-ml reaction tank together with a stirrer, and 79.29 mL of a mixed solvent of ethanol (EtOH) and tetrahydrofuran (THF) was added (the amount of tetrahydrofuran (THF) and acetonitrile (ACN) used was 510.5 parts by volume relative to 1.0 part by volume of ethanol (EtOH) (acetonitrile (ACN) was not used), ethanol:tetrahydrofuran:acetonitrile = 0.00196:1:0 (volume ratio)), and the mixture was stirred with a magnetic stirrer for 10 minutes for mixing.

[0342] Then, using a vacuum pump and an oil bath, heating was performed under reduced pressure at room temperature (20°C) for 1 hour (first heating-1), and heating was performed under reduced pressure at 130°C for 1 hour (first heating-2). Furthermore, the powder obtained by the first heating was heated under reduced pressure at 200°C for 2 hours (second heating-1) to obtain a powder.

[0343] The powder obtained by heating at 130°C in the first heating and 200°C in the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum of the powder obtained by heating at 130°C is shown in FIG. Fig.21 The X-ray diffraction spectrum of the powder obtained by heating at 200°C is shown in Fig. 22 (The X-ray diffraction spectra in these figures also include those of Example 12 and Comparative Example 3.) In addition, the ion conductivity of the powder obtained by heating at 200° C. in Example 13 was measured. The results are shown in Table 2.

[0344] (Example 14)

[0345] In Example 13, except that the amount of the solvent used was set to the amount shown in Table 2, a powder was obtained in the same manner as in Example 13.

[0346] The powder obtained by heating at 130°C in the first heating and 200°C in the second heating was subjected to powder XRD diffraction measurement. The X-ray diffraction spectrum of the powder obtained by heating at 130°C is shown in FIG. Fig.21 The X-ray diffraction spectrum of the powder obtained by heating at 200°C is shown in Fig. 22 (The X-ray diffraction spectra in these figures also include those of Example 12 and Comparative Example 3.) In addition, the ion conductivity of the powder obtained by heating at 200° C. in Example 14 was measured. The results are shown in Table 2.

[0347] (Comparative Example 3)

[0348] The powder of Comparative Example 3 was obtained in the same manner as in Example 12 except that the amount of sulfur used was changed from 0.3616 g to 0.1808 g. The X-ray diffraction spectrum of the powder obtained by heating at 130° C. in Comparative Example 3 is shown in FIG. Fig.13 and 21 The X-ray diffraction spectrum of the powder obtained by heating at 170°C is shown in Fig.14 and 22 .

[0349] In addition, for Example 12 and Comparative Example 3, the raw materials and solvents used, and the amount of elemental sulfur used are summarized in the following Table 2.

[0350] [Table 3]

[0351] Table 2

[0352]

[0353] *1. Raw material supply methods D and E are as follows.

[0354] D: Mix lithium sulfide, phosphorus pentasulfide and elemental sulfur, and then mix with lithium iodide.

[0355] E: Mix lithium sulfide, phosphorus pentasulfide, elemental sulfur, lithium iodide and lithium bromide at the same time.

[0356] like Fig.13 and 14 (as well as Fig.21 and 22 ), the powder obtained in Example 12 has peaks derived from the sulfide crystallized lithium superion conductor region type II crystal structure at 2θ=20.3° and 23.9°, and thus is confirmed to be a sulfide solid electrolyte having a sulfide crystallized lithium superion conductor region type II crystal structure. It is known that a sulfide solid electrolyte having a sulfide crystallized lithium superion conductor region type II crystal structure is a sulfide solid electrolyte having high ionic conductivity like the above-mentioned sulfide solid electrolyte having an argyrodite type crystal structure, and the powder obtained in Example 12 is considered to be a sulfide solid electrolyte having high ionic conductivity.

[0357] like Fig.13 and 14 (as well as Fig.21 and 22 ), the powder obtained in Comparative Example 3 did not observe peaks derived from the type II crystal structure in the sulfide crystal lithium superion conductor region at 2θ=20.3° and 23.9°, and peaks believed to be derived from Li7P2S8I or Li4PS4I were observed at 2θ=20.8° and 27.9°. In addition, a peak due to lithium sulfide was also confirmed at 2θ=27.0°, indicating that the reaction did not proceed efficiently.

[0358] Examples 13 and 14 are examples of using alcohol solvents and ether solvents as solvents. The powders obtained in these examples are as follows Fig.21 and 22 As shown, similarly to the powder obtained in Example 12, there are peaks at 2θ=20.3° and 23.9° originating from the type II crystal structure of the sulfide crystallized lithium superion conductor region, confirming that it is a sulfide solid electrolyte having the type II crystal structure of the sulfide crystallized lithium superion conductor region and has high ionic conductivity.

[0359] Industrial Applicability

[0360] According to the method for producing a sulfide solid electrolyte of the present embodiment, a sulfide solid electrolyte having improved ion conductivity can be efficiently provided. The sulfide solid electrolyte obtained by the production method of the present embodiment is suitable for use in batteries, particularly batteries used in information-related devices or communication devices such as personal computers, cameras, and mobile phones.

Claims

1. A method for producing a sulfide solid electrolyte, characterized in that: include: Mixing a raw material containing a plurality of raw materials in a solvent, wherein the raw materials contain at least one atom selected from lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms; as well as Then heating, The raw material contains elemental sulfur and lithium sulfide, The amount of the elemental sulfur used is greater than 1.0 mol relative to 1.0 mol of the lithium sulfide.

2. The method for producing a sulfide solid electrolyte according to claim 1, wherein: The halogen atom is at least one atom selected from a chlorine atom, a bromine atom, and an iodine atom.

3. The method for producing a sulfide solid electrolyte according to claim 1 or 2, wherein: The solvent is an organic solvent containing at least one atom selected from oxygen atoms and nitrogen atoms.

4. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 3, wherein: The solvent is at least one organic solvent selected from alcohol solvents, ether solvents and nitrile solvents.

5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, wherein: The solvent includes an alcohol solvent.

6. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 5, wherein: The solvent includes an alcohol solvent and at least one organic solvent selected from an ether solvent and a nitrile solvent.

7. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 6, wherein: The solvent is an organic solvent including an alcohol solvent, an ether solvent and a nitrile solvent.

8. The method for producing a sulfide solid electrolyte according to any one of claims 5 to 7, wherein: The alcohol solvent is used in an amount of 0.005 mol or more and 20.0 mol or less relative to 1.0 mol of the lithium sulfide.

9. The method for producing a sulfide solid electrolyte according to any one of claims 6 to 8, wherein: The total amount of the ether solvent and the nitrile solvent used is 2.0 parts by volume or more and 10000.0 parts by volume or less relative to 1.0 part by volume of the alcohol solvent used.

10. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 9, wherein: The heating temperature during the heating is 20° C. or higher and 500° C. or lower.

11. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 10, wherein: The heating is performed by first heating at a heating temperature of 20° C. or higher and lower than 150° C. and second heating at a heating temperature of 150° C. or higher and 500° C. or lower.

12. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 11, wherein: When the mixing is performed, the raw materials are mixed simultaneously.

13. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 11, wherein: In the mixing, a raw material group 1 including a part of raw materials selected from the raw materials is mixed, and then a raw material group 2 including raw materials other than the part of raw materials is mixed.

14. The method for producing a sulfide solid electrolyte according to claim 13, wherein: The raw material group 1 contains elemental sulfur.

15. The method for producing a sulfide solid electrolyte according to claim 13 or 14, wherein: The raw material group 1 includes a raw material containing at least one atom selected from lithium atoms, phosphorus atoms, and sulfur atoms, elemental sulfur, and lithium sulfide, and the raw material group 2 includes a raw material containing a halogen atom.

16. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 15, wherein: A crystalline sulfide solid electrolyte having an argyrodite-type crystal structure or a sulfide crystalline lithium superion conductor region-type II crystal structure is produced.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same

    JP2014191899A

  • Production method of solid electrolyte

    WO2014192309A1

  • Solid lithium electrolytes and process of production

    WO2018054709A1

  • Method for producing solid electrolyte, and electrolyte precursor

    WO2020105737A1